Case Study of Cutaneous Mercury Granuloma - Bothale , Kalpana (Advancement and New Understanding in Medical Science Vol. 9, 2024)
Human contact with mercury has been ongoing for centuries and has been previously considered a legitimate means of treating different Cutaneous and systemic conditions. Cutaneous mercury granuloma is rarely encountered. Clinically it may pose difficulty in diagnosis. Here, we report a 23-year-old male presented with erythematous, nodular lesions over the forearm and anterior aspect of chest wall. X-ray showed diffuse deposition of metallic material (mercury) in the soft-tissue upto subcutaneous plane in the left forearm and chest wall. Metallic mercury in tissue sections appear as dark black, opaque, spherical globules of varying size and number. They are surrounded by granulomatous foreign-body reaction. It is composed of foreign body giant cells and mixed inflammatory infiltrate composed of histiocytes, lymphocytes, plasma cells, and few eosinophils.